RESEÑA de : González Yanci, P.; Aguilera Arilla, M.; Borderías Uribeondo, P.; Santos Preciado, J.M. Las Rocas y el Relieve. Madrid : UNED, GEMAV, 1995 - Espacio, Tiempo y Forma. Serie VI, - (Espacio Tiempo y Forma. Serie VI, Geografía, 1995)
-